Academic Environmental Narratives: A study in the Light of Audiovisual Methodologies - Fernandez Bouzo, Maria Soledad (2017)
Beginning about a decade ago, it has been possible to observe in Argentina the emergence of documentary productions on environmental issues shot by university groups along with community social actors. The guiding questions of this work are: What do this type of environmental documentaries tell? What are their stories and images about the environment? What environmental struggles do they reveal? Do they show scientific research findings, collective action plans, or both? Based on a methodological approach that allows for an audiovisual narrative analysis, this article aims to understand how stories and images about the environment are constructed within the domain of scholars and the university, together with community actors. To this end, experiences of audiovisual creations by two Argentine universities are studied. The productions have been made in collaboration with environmental community organizations between 2007 and 2009. The methodology of analytical decomposition-recomposition of audiovisual language provides a tool that allows us to trace the process of image and sound construction when related to environmental issues.This work belongs to the field of socio-environmental studies and is based on the developments of qualitative audiovisual methodology in sociology; it is also part of a wider framework of interest on production, social mobilization and circulation of audiovisual images related to environmental issues, in particular, images of documentary nature.